Twórcza reinterpretacja mitów narodowych. Próba współodczytania „Trans-Atlantyku” Witolda Gombrowicza i „Małego palca Buddy” Wiktora Pielewina - Jaworski, Mateusz (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of this paper is to depict significant parallels between the works of Witold Gombrowicz and Viktor Pelevin within the scope of reinterpreting national myths. In their novels, Trans Atlantic and Buddha’s Little Finger, the writers seem to take account of substantial danger related to fixed, ossified forms of understanding the notions of nation and motherland. Despite visible differences in their styles both novelist stay alert to automatized relationship to any phenomenon and make attempts at provoking the reader to rethink their relationship to the abovementioned terms. The author of the present paper finds these issues crucial and very up-to-date in the post postmodern society and culture, in particular in light of the recent geopolitical changes.